Perlindungan Hukum Bagi Pencipta Yang Ciptaannya Digunakan Dalam Aplikasi Tiktok Menurut Undang Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Panjaitan, Wijaya Natalia (KANJOLI Business Law Review, 2023)
Tiktok is an application that is currently popular as a platform for creativity because it is filled with a selection of songs or music that can be created in the form of fragments of a few seconds to some in the form of full music, which is a copyrighted work whose use must be with the permission of the creator. The existence of the Tiktok application that uses songs belonging to the creator without permission can be said to have violated copyright, so the creator needs to get legal protection because if this is allowed it will harm the creator and the state. The research method used is normative juridical by using the approach of law number 28 of 2014 on copyright, conceptual approach and case approach. The results showed that creators who create works that are then used in the Tiktok application must have legal protection under the Copyright Law in Indonesia.